2013
DOI: 10.1002/bjs.9196
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of additional technologies to enhance angioplasty for infrainguinal peripheral arterial occlusive disease

Abstract: Background: There are several additional techniques designed to enhance conventional percutaneous transluminal balloon angioplasty (PTA). This systematic review assessed current evidence on the clinical effectiveness of additional techniques for infrainguinal peripheral arterial occlusive disease (PAD).Methods: Relevant electronic databases, including MEDLINE, were searched in May 2011. The population comprised participants with symptomatic PAD undergoing endovascular treatment for disease distal to the inguin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…11 While current guidelines and systematic reviews favour stenting and drug-coated devices to treat lesions above the knee, PTA alone remains the gold standard for treatment below the knee. 12 Furthermore, the significantly lower DAP values in surgical units might be explained by non-surgical units being more prone to solve even complex lesions in advanced diseases by endovascular means as their sole option of treatment. The vascular surgeon may be more likely however to outweigh catheter based treatment options for complex lesions with alternatives of open reconstructions.…”
Section: Discussionmentioning
confidence: 99%
“…11 While current guidelines and systematic reviews favour stenting and drug-coated devices to treat lesions above the knee, PTA alone remains the gold standard for treatment below the knee. 12 Furthermore, the significantly lower DAP values in surgical units might be explained by non-surgical units being more prone to solve even complex lesions in advanced diseases by endovascular means as their sole option of treatment. The vascular surgeon may be more likely however to outweigh catheter based treatment options for complex lesions with alternatives of open reconstructions.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent meta-analysis including a total 40 randomized trials, Simpson et al [13] sought to determine whether patients undergoing endovascular treatment for femoro-popliteal artery stenosis/occlusion benefited from additional techniques including self-expanding stents, drug-coated balloons, and drug-eluting stents. The authors reported that self-expanding stents were associated with a lower restenosis rate at 6 months and also that stent grafting significantly reduced restenosis compared to percutaneous transluminal angioplasty alone.…”
Section: Discussionmentioning
confidence: 99%
“…It was assumed that all re-interventions performed were either bypass surgery (for acute failure; defined as within 30 days) or PTA with bail-out BMS (for failure after 30 days). A systematic review and meta-analysis were carried out to generate data on clinical effectiveness 6. Searches were conducted in May 2011.…”
Section: Methodsmentioning
confidence: 99%